Legal Reconstruction Return on Assets In Money Laundering Crimes In the Department of Justice Value-Based Forestry - Safrin Ritonga; Anis Mashdurohatun; Sri Endah Wahyuningsih (International Journal Reglement & Society (IJRS), 2023)
In the current Money Laundering Act of the Ministry of Forestry and to find the reconstruction of the Asset Recovery Law In The  Crime Of Money Laundering In The Department Of Forestry Based On The Value Of Justice.  Asset Recovery in  Money Laundering Crimes in the  Ministry of Forestry Has Not Been Based on the Value of Justice, because the phrase "original criminal investigator" in Article 74 of the TPPU Law gives the definition of an original criminal investigator is an official from an agency who by law is authorized to conduct investigations in accordance with the provisions of the procedural law and the provisions of laws and regulations  in this case, all investigators who investigate the original criminal act or criminal act that later gave birth to the criminal act of money laundering. Legal Weaknesses of Asset Recovery In The  Current Money Laundering Act In The Ministry Of Forestry.   Reconstruction  of the Asset Recovery Law in the Criminal  Act of Money Laundering in the  Ministry of Forestry Based on the Value of Justice, by reconstructing the Explanation of Article 74 of Law 8/2010, the investigator of the original criminal act is immediately attached to his authority to investigate the criminal act of money laundering as long as the original crime includes a criminal act as regulated in Article 2 paragraph (1)  TPPU Law